The Histidin-rich Glycoprotein Pro186/Ser Polymorphism Is not Related to Myocardial Infarction in the ECTIM Study - Herrmann, Stefan-Martin; Poirier, Odette; Nicaud, Viviane; Ruidavets, Jean-Bernard; Evans, Alun; Arveiler, Dominique; Luc, Gerald; Bara, Lucienne; Cambien, François (Thrombosis and Haemostasis, 1998)
The histidin-rich glycoprotein (HRG) may contribute to coronary heart disease as a consequence of its possible thrombophilic properties. To test this hypothesis we have investigated the Pro186/Ser polymorphism of the HRG gene, which is known to strongly affect plasma HRG levels, in a large multicenter case-control study of myocardial infarction (MI). The results failed to demonstrate any association between the polymorphism and MI or angiographically assessed coronary stenosis.